Formative evaluation of Helderberg Association for persons with disabilities - Bothma, Zani (School of Management Studies, 2019)
Purpose The peer support programme as run by Helderberg Association for Persons with Disabilities (HAPD) uses people who have disabilities to support people with disabilities in their own community. The purpose of this formative evaluation is to explore the roles and responsibilities of peer supporters and the needs in the community. This evaluation would help HAPD explore which areas of the peer support programme could be improved. The evaluation explored the relationship between addressable and non-addressable needs, the types of disabilities and the needs identified of the people with disabilities. Exploring these relationships would allow HAPD to understand which needs they are more likely to address and which areas they could improve their support in.